Alternative Community Empowerment Program As An Effort To Improve Street Vendors' Empowerment In Jayapura City - La Maga; Rachmaeny Indahyani (AIBPM Publisher, 2025)
The economic recession due to the Covid-19 pandemic has had a very significant impact on Street Vendors (PKL). This situation has triggered an increase in the economic burden on families, even though the government has provided social assistance. Providing assistance to street vendors is an indication that they have a low level of empowerment. The purpose of this study was to formulate a form of street vendor empowerment program in Jayapura City. The analysis was carried out using the AHP method with the assistance of the ExpertChoice 11 program, involving several related agencies as respondents. The low ability of street vendors in business management is the main obstacle in empowering street vendors. The aspect of training institutions for street vendors that has not been maximized is the main cause of the low ability of street vendors in business management, the low ability of street vendors in innovating, and the products produced by street vendors are relatively uniform. Increasing innovation and business management skills through education and training is an empowerment program that can be carried out for street vendors.